On a Nonlocal Damping Model in Ferromagnetism. (15th July 2015) - Moumni, M.; Tilioua, M.
Abstract : We consider a mathematical model describing nonlocal damping in magnetization dynamics. The model consists of a modified form of the Landau-Lifshitz-Gilbert (LLG) equation for the evolution of the magnetization vector in a rigid ferromagnet. We give a global existence result and characterize the long time behaviour of the obtained solutions. The sensitivity of the model with respect to large and small nonlocal damping parameters is also discussed.